Edukasi Penggunaan Energi Listrik dan Fasilitas Kantor yang Efisien dan Aman - Arsadiando, Watra; Sutikno, Tole; Handayani, Lina; Wahono, Tri (LOSARI DIGITAL, 2025)
The inefficient use of electrical energy and office facilities often leads to waste, equipment damage, and potential workplace hazards. This community service program focused on educating employees to use electricity and office facilities in a safe and efficient manner. The objectives were to raise awareness of safety and efficiency, reduce energy consumption and the risk of facility damage, and enhance professionalism in the use of office equipment. The program was implemented through an interactive online workshop via Zoom, consisting of a pre-test, delivery of materials and practical sessions on five key indicators (electrical devices, computers, air conditioners, lighting, and electrical panels), a post-test, and reflective discussions. The results demonstrated a significant improvement in participants’ understanding, as indicated by higher average post-test scores compared to pre-test results. Moreover, participants were able to identify risks of improper electricity use and apply energy-saving strategies. This activity successfully fostered a safer, more efficient, and professional work environment. In the future, further programs are needed to monitor work behavior, strengthen internal policies, and integrate energy-saving technologies to ensure the sustainability of these positive impacts.